motives, benefits, and problems of conversion to organic production - Cranfield, John; Henson, Spencer; Holliday, James (Agriculture and human values, 2010)
Using data from a survey of certified organic or in-transition to organic vegetable and dairy producers in Canada, we seek to understand a farmer's decision to convert to organic production by exploring the motives, problems and challenges, and benefits of transition to organic. Results suggest that health and safety concerns and environmental issues are the predominant motives for conversion, while economic motives are of lesser importance. In contrast to the extant literature, results suggest that the motives underlying transition have not changed overtime in Canada. Problems experienced during transition relate to lack of governmental and institutional support, negative pressure from other farmers and farm groups, and lack of physical and financial capital. Reduced exposure to chemicals and improved food quality were highly ranked benefits, while economic related benefits were scored among the lowest of the listed benefits. To prosper, the Canadian organic sector must overcome fundamental marketing problems and challenges. Promulgation of the Canada Organic standard may help address some marketing issues by providing more information to consumers.